2005
DOI: 10.1111/j.1468-1331.2005.01073.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of status epilepticus in a rural area of northern Italy: a 2‐year population‐based study

Abstract: We performed a 2-year population-based study on status epilepticus (SE) in adults in the rural area of Lugo di Romagna, northern Italy, to verify whether an area of low-level urbanization has a lower risk of occurrence of SE (as recently suggested), different clinical features and short-term prognosis than areas of high-level urbanization. We found crude and age- and sex-adjusted annual incidence rates of SE of 16.5/100 000 and 11.6/100 000, respectively. In patients under 60 years crude incidence was 2.9/100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
9
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(105 citation statements)
references
References 10 publications
6
89
9
1
Order By: Relevance
“…The study showed that the incidence of SE in the HD of Fe, a well-defined population in southern Europe, is 27.2/100,000/year -higher than that reported in the previous European studies, [1][2][3][4] showing that the SE risk in southern Europe is more similar to that estimated in the US. 5,6 The SE incidence in the adult population (24.0/100,000/year), as estimated in other European studies, 1,3,4 is still the highest reported in Europe.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The study showed that the incidence of SE in the HD of Fe, a well-defined population in southern Europe, is 27.2/100,000/year -higher than that reported in the previous European studies, [1][2][3][4] showing that the SE risk in southern Europe is more similar to that estimated in the US. 5,6 The SE incidence in the adult population (24.0/100,000/year), as estimated in other European studies, 1,3,4 is still the highest reported in Europe.…”
Section: Discussionmentioning
confidence: 50%
“…5,6 The SE incidence in the adult population (24.0/100,000/year), as estimated in other European studies, 1,3,4 is still the highest reported in Europe. [1][2][3][4] Most of the current findings are consistent with the other European and American studies. [2][3][4][5][6] …”
Section: Discussionmentioning
confidence: 77%
“…Dunnes et al [37] estimate that NCSE constitutes 20% of all status epilepticus in adults. Recent populations-based studies have reported a higher percentage of NCSE among all status epilepticus (30% to 60%) [38][39][40][41][42]. This wide range is explained by the difference in NCSE definition, classification and probably the differences in population characteristics.…”
Section: Epidemiology Of Ncsementioning
confidence: 98%
“…Status epilepticus (SE) is one of the major neurological emergencies with an incidence of about 20/100,000 for the causasian population in industrialized countries [Chin et al 2006;Vignatelli et al 2005Vignatelli et al , 2003Knake et al 2001;Coeytaux et al 2000;Jallon et al 1999]. SE has usually been defined as a single clinical seizure lasting more than 30 min or repeated seizures over a period of more than 30 min without intervening recovery of consciousness [Knake et al 2001;DeLorenzo et al 1995; Epilepsy Foundation of America's Working Group, 1993;Hauser, 1990].…”
Section: Introductionmentioning
confidence: 99%